The bonds of family : slavery, commerce and culture in the British Atlantic world - Donington, Katie (Manchester University Press, 2019)
Moving between Britain and Jamaica this book reconstructs the world of commerce, consumption and cultivation sustained through an extended engagement with the business of slavery. Transatlantic slavery was both shaping of and shaped by the dynamic networks of family that established Britain's Caribbean empire. Tracing the activities of a single extended family - the Hibberts - this book explores how slavery impacted on the social, cultural, economic and political landscape of Britain. It is a history of trade, colonisation, enrichment and the tangled web of relations that gave meaning to the transatlantic world. The Hibberts's trans-generational story imbricates the personal and the political, the private and the public, the local and the global. It is both the intimate narrative of a family and an analytical frame through which to explore Britain's history and legacies of slavery.
Keywords: Hibbert family.; Hibbert family; Slavery -- Great Britain -- Colonies -- History.; Slavery -- Jamaica -- History.; Slavery -- Colonies; Slavery; Slavery -- British colonies; Great Britain; Jamaica; HISTORY / United States / Colonial Period (1600-1775); History